Effectiveness of Implementing the Pickleball Sports Training Model for Middle Age People 45 – 54 Years Old among Journalists in Surabaya - Muchamad Arif Al Ardha; Panji Bana; Kolektus Oky; Dani Primanata; Sauqi Sawa Bikalawan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The study evaluates the effectiveness of implementing a pickleball training model for middle-aged journalists in Surabaya, focusing on those aged 45-54. The research utilizes a quantitative one-group pretest-posttest design, with 33 male journalists participating. Over three weeks, participants engaged in eight pickleball training sessions. The study measures improvements in executing forehand, backhand, and serve shots using observational criteria. IBM SPSS Statistics 26 was employed for data analysis, using the Wilcoxon signed-rank test due to the non-normal distribution of data. Results indicate significant improvements in all measured skills, evidenced by a p-value < 0.05. The average skill improvement was 65.53%, with specific gains in forehand, backhand, and serve skills noted. These findings suggest that pickleball not only enhances physical fitness but also contributes positively to emotional well-being, thanks to the enjoyable and social nature of the sport. The study highlights pickleball's low injury risk and its suitability for middle-aged individuals, promoting both physical health and social interaction. However, the absence of a control group is a limitation; future research should consider comparative studies to validate these findings further. Overall, pickleball appears to be an effective, enjoyable form of exercise for middle-aged professionals, enhancing both physical and psychological health.